Prohibited Force - Pobjie, Erin (Cambridge University Press, 2024)
Erin Pobjie offers an original framework to identify prohibited 'uses of force' under article 2(4) UN Charter and customary international law. With a range of illustrative case studies, Pobjie demonstrates the validity and usefulness of this theoretical framework in real-world practice.